Incorporating Screencasts In Online Teaching - Peterson, Elaine (International Review of Research in Open and Distributed Learning, 2007)
Despite success in teaching the class ‘Organization of Information in a School Library Media Center’ (EDCI 545) online, one component continued to be a problem for students, the Dewey Decimal Classification System. To supplement the instruction, a set of simple screencasts was developed to assist distance education students. Benchmarks were established and a beta test conducted. It is expected that the next online class of students will have increased success because of the addition of screencasts. It is suggested that screencasts be considered as an additional tool for online learners across other disciplines, particularly when using databases that have layered sets of information, requiring multiple mouse clicks.